Benign endotracheal tumor (hamartoma) mimicking bronchial asthma - Kaziród, Tomasz; Tokarski, Sławomir; Kaznowska, Ewa; Rzeszutko-Grabowska, Magdalena (European Journal of Clinical and Experimental Medicine, 2024)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. The most common benign tumor of the lung is hamartoma. In many cases, it is a spherical tumor, located peripherally, often without clinical symptoms. Predominantly it is found accidentally during radiological examination. In some cases the tumor reaches a significant size in the lung parenchyma or in the lumen of the bronchi or trachea. Then, symptoms such as cough, dyspnea, wheezing, less commonly hemoptysis, and chest pain may occur. In addition, tumors located endobronchial or endotracheal may cause recurrent pneumonia or mimic obstructive diseases of the lower respiratory tract such as chronic obstructive pulmonary disease, or bronchial asthma. We present the case of a patient with an endotracheal tumor mimicking bronchial asthma. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Description of the case. A 53-year-old male was taking bronchodilators and inhaled steroids for several months. The baseline chest radiograph showed no abnormalities. Spirometry suggested an obstruction of respiratory flow in the central or upper airways. The lack of improvement after asthma treatment required an extension of the diagnosis. Computed tomography allowed accurate visualization of the tumor lesion of the trachea, which was significantly obstructing its lumen, and resection was carried out. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Our case demonstrates that tracheal tumors can present symptoms similar to respiratory tract diseases. In unresolved cases, spirometry and computed tomography are helpful in proper diagnosis.